PENGARUH BEBAN KERJA, SCHEDULE/SHIFT DAN STRESS TERHADAP NILAI MAHASISWA STEIN ANGKATAN 2012 - Chatarina Yunita Tarigan (Panorama Nusantara, 2016)
This study aims to determine the effect of workload, stress and schedule of work simultaneously toward student grades. The population used in this study was 90 respondents. The sample in this study were 70 respondents using non-probability sampling. Respondents in this study were STEIN students of 2012 who take courses in Public Relations. Data were collected and analyzed using SPSS version 20. Classic assumption test including normality test, multicollinearity, heteroscedasticity, and linearity. R -Square summarized in the regression model for 0.931 that shows the influence of the workload , schedule / shift , and stress work simultaneously toward student grades by 93.1% while the remaining 6.9% is influenced by other factors that not included in this study.